(untitled) - Maroulis, Zacharias B. (Boca Raton, FL, 2008)
Applying the proven success of process engineering economics to the food industry, this book/CD-ROM package considers the design and economic analysis of food ingredients, food manufacturing, and food preservation plants. Early chapters give background material on research technology, the structure of the food system in the US and EU, and principles of food plant design. Later chapters apply concepts of capital cost, operating cost, and cash flow to estimations of plant profitability. These chapters explain data and models for estimating capital investment and operating costs, in application areas of specific types of food preservation and manufacturing plants, including tomato paste, orange juice concentrate, bread, and wine.
Keywords: Food industry and trade.,Chemical engineering.,Chemical plants.,Công nghệ hóa học